Mixed Finite Element Computation of Energy Release Rate in Anisotropic Materials Based on Virtual Crack Closure-Integral Method (Fracture and Structural Integrity, 2021)
The material with anisotropic properties are becoming widely essential due to the ease to manipulate their mechanical properties in order to obtain a particular quality, insure safety or a specific behavior. Those kind of materials are considered anisotropic because their characteristics and behavior are dependent to every direction of the material’s orientation.In this work, the virtual crack closure-integral technique is implemented to a mixed finite element, in addition with the stiffness derivative procedure, to evaluate the energy release rate of crack extension in anisotropic materials. A simulation of a cracked edge rectangular plat with anisotropic characteristics is taken for example.The results obtained are in good agreement with the analytical results, making the proposed technique a good model for fracture investigation and allow it to study more complicated cases in future works.
Keywords: Fracture Mechanics; Finite Element Method; Anisotropy; Energy Release Rate; Virtual Crack Closure-Integral method